Patterns of use of oral health care services in Australian rural adults: the Crossroads‐II Dental sub‐study. (10th July 2021) - Mariño, R; Glenister, K; Bourke, L; Morgan, M; Atala‐Acevedo, C; Simmons, D
Abstract: Background: As part of a larger study, the Crossroads‐II Dental sub‐study determined the patterns of, and barriers to, oral health care service utilization in a rural area of Victoria. Methods: In this cross‐sectional sub‐study predisposing, enabling, needs‐related, and oral health variables were considered in association with patterns of oral health care utilization. A logistic regression was performed to explain the use of oral health care services. Results: Overall, 574 adults participated, with 50.9% reporting having visited an oral health care service in the previous 12 months. Age, number of chronic health conditions and holding a health card; were associated with increased visit to a dentist (OR = 1.01; 95% CI: 1.00–1.03; OR = 1.08; 95% CI: 1.01–1.16; OR = 2.06; 95% CI: 1.26–3.36, respectively). Perceived barriers to care and number of missing teeth decreased the odds of using services (OR = 0.46; 95% CI: 0.36–0.58; OR = 0.95; 95% CI: 0.92–0.98, respectively). Conclusions: Results suggest that use of oral health care services is associated with a range of financial, educational, health and structural barriers. Increasing the use of oral health care services in rural populations requires additional efforts beyond the reduction of financial barriers.